Preserved auditory-motor synchronization during finger-tapping to music and metronomes at various tempi in progressive multiple sclerosis - Vanbilsen, Nele; Feys, Peter; Rosso, Mattia; Van Wijmeersch, Bart; Kos, Daphne; Leman, Marc; Kotz, Sonja A.; Moumdjian, Lousin (Frontiers in Neurology, 2025)
BackgroundPersons with relapsing and remitting multiple sclerosis (MS) can synchronize steps with music and metronomes at different tempi. However, progressing demyelination, loss of neural connectivity and increased cognitive impairment likely affects how persons with progressive MS (PwPMS) synchronize movements with external beats. We tested how PwPMS tap to music and metronomes at high and low tempi in order to understand auditory-motor capacities behaviorally in PwPMS. Synchronization at brain level was measured using EEG. We aim (1) to investigate whether PwPMS can synchronize taps to various tempi and musical structures (music and metronomes) compared to healthy controls (HCs) (2) to measure neural entrainment to understand the neural basis of synchronization.MethodsParticipants synchronized finger taps to beats in music and metronomes at five tempi: preferred tapping frequency (0%), slow (−8, −4%), and fast (4, 8%). A mixed model analyzed synchronization outcomes, while regression identified clinical factors affecting consistency. Spearman-rank correlations assessed correlations between neural entrainment and behavioral synchronization consistency.ResultsSixteen HCs and nineteen PwPMS (mean age = 52.42, mean EDSS = 4.24) participated. No significant differences were seen in behavioral and neural synchronization outcomes between PwPMS and HCs across tempi. Behaviorally, synchronization was higher with the metronomes than with music (p = 0.01), yet non-significant at neural level. Disability (p = 0.02) and manual dexterity (p < 0.001) affected synchronization consistency for metronomes, while cognitive impairment affected synchronization consistency for music.ConclusionPwPMS show preserved auditory-motor synchronization capacities however influenced by motor and cognitive factors. The study results support considering the use of auditory-motor synchronization for rehabilitation of PwPMS.